2015
DOI: 10.1007/s00213-015-4047-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment history and drug-placebo separation in a placebo-controlled trial in major depressive disorder

Abstract: Treatment history appears to constitute a factor that is distinct from other commonly studied illness characteristics or expectancy measures, and that impacts overall response as well as drug-placebo separation in RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Depressive symptoms were generally responsive to treatment with the DA agonist pramipexole, suggesting DA system mediation of treatment response. Inference of a specific dopaminergic mechanism of response, however, is limited by absence of a placebo treatment group and likelihood of nonspecific influences in an antidepressant-naive sample (85). …”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were generally responsive to treatment with the DA agonist pramipexole, suggesting DA system mediation of treatment response. Inference of a specific dopaminergic mechanism of response, however, is limited by absence of a placebo treatment group and likelihood of nonspecific influences in an antidepressant-naive sample (85). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the variation in effect size may be attributed to the difference in response to placebo, rather than difference in response to augmentation. Indeed, a recent study has shown lower placebo response rates in patients who have failed more prior active treatments(4). There may be biological differences in those who are nonresponsive to 2 or more antidepressants where a multi-receptor approach is required and achieved by combination of 2 different drugs classes.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies conducted by Aimee Hunter and colleagues at UCLA provide indirect support for this hypothesis (53, 54). In each of these studies, depressed patients in clinical trials were grouped according to whether they had ever been on antidepressants before.…”
Section: Is There a Drug Effect At All?mentioning
confidence: 99%